2020
DOI: 10.1039/c9ra08409f
|View full text |Cite
|
Sign up to set email alerts
|

Production of green diesel from catalytic deoxygenation of chicken fat oil over a series binary metal oxide-supported MWCNTs

Abstract: Deoxygenation processes that exploit milder reaction conditions under H2-free atmospheres appear environmentally and economically effective for the production of green diesel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 65 publications
3
32
0
Order By: Relevance
“…Most of the liquid products produced higher yields of n-C 15 , hence it was proposed that the mild cracking occurred through C-C cleavage from the n-C 17 fraction and produced large amounts of n-C 15 (pathway D). This was in agreement with the results of Aliana-Nasharuddin et al, 42 who produced high n-C 15 fractions in the catalytic deoxygenation of chicken fat oil.…”
Section: Deoxygenation Activity Of Wcosupporting
confidence: 93%
See 3 more Smart Citations
“…Most of the liquid products produced higher yields of n-C 15 , hence it was proposed that the mild cracking occurred through C-C cleavage from the n-C 17 fraction and produced large amounts of n-C 15 (pathway D). This was in agreement with the results of Aliana-Nasharuddin et al, 42 who produced high n-C 15 fractions in the catalytic deoxygenation of chicken fat oil.…”
Section: Deoxygenation Activity Of Wcosupporting
confidence: 93%
“…4 displays the thermal stability proles for AC and binary metal oxide-supported AC catalysts. The results revealed that AC rendered three stages of weight loss: 100-200 C, 210-420 C, and 430-850 C. The beginning weight loss was assigned to the loss of H 2 O molecules at about 6.7 wt%, 31,42,57 the second weight loss was associated with the decomposition of cellulose at about 11.2 wt% and the third major weight loss was about 40.5 wt%, due to the decomposition of carbonaceous compounds. 58,59 In contrast to binary metal oxide-supported AC catalysts, a minor weight loss of less than 35 wt% due to carbonaceous materials was observed at decomposition temperatures above 600 C. This nding proves that the presence of metal oxides on AC as support gives signicant thermodynamic stability to the parent AC.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, the process of TPR analysis also confirmed that three stages were reduced based on MoO3 and MoP. The results indicated that the activity of the catalysts decreased by which MoP was divided by TiO2 over the period because the catalyst deactivation and the activity showed variations that were not associated with significantly different pressures and the H2/oil ratio [14].…”
Section: Hdo (Hydrodeoxygenation)mentioning
confidence: 66%